The prospect of using the finite element method and ansys for mathematical modeling of thermo-mechanical calibration large axisymmetric structures with high requirements for the geometric accuracy - Sherstiuk, D. G.; Kulik, A. V.; Gladkiy, M. A. (Видавництво Львівської політехніки, 2013)
За допомогою математичного моделювання визначено напружено-деформований стан осесиметричної конструкції та технологічної оправки під час термомеханічного калібрування. Термомеханічне калібрування визначається багатьма взаємозалежними факторами, що впливають на остаточний результат, і його відповідність строгим вимогам точності. Методом кінцевих елементів за допомогою числового моделювання у програмному середовищі ANSYS встановлена відповідність розрахункових параметрів відносно реального процесу термомеханічного калібрування. The article carries out using mathematical modeling of the definition of the shells stressstrain state and technological mandrel in the process of thermo-mechanical calibration. Thermo-mechanical calibration determined by many interrelated factors that affect the final result, and its compliance with the stringent requirements of accuracy. The finite element method for using the numerical simulation in ANSYS corresponded between the calculated parameters with respect to the real thermo-calibration process.